Efeitos do laser de baixa intensidade no processo de cicatrização em ratos jovens e idosos: estudo morfométrico e morfológico - Ferreira, Márcio Antônio (2006)
The rise of life expectation has brought forth many problems and others will come with the aging process including the cicatrization of aged tissues Therefore many researches with low potency laser (LPL) to enhance cicatrization are outstanding although tested in young tissues A comparative morphologic and morphometric study aimed at verifying the effects of the application of LPL 660 nm on cicatrization in young and old rats Forty male Wistar rats (Rattus norvegicus albinos) were separated into four similar groups 10 treated young rats (TYR) 10 young control rats (CYR) 10 treated old rats (TOR) and 10 old control rats (COR for the daily application of LPL 660 nm with 3 J/cm2 30 mW potency during 7 days The control groups were submitted to the same procedures but the laser apparatus was turned off After surgical excision with a metal punch a pachimeter was used to measure the wound in both frontal and sagittal axes (initial and final) Likewise the wound was photographed from top to bottom with a TEKPIX digital camera with 3.1 megapixels and the same distance of 15 cm was maintained without close-ups zoom or macro for all the groups The photos were captured by a specific software (ImageLab) where the area of the wound was duly demarcated in centimeters in the beginning and end of the experiment 1st and 7th day respectively Histological glass slides were prepared and sent to the Laboratory of Pathologic Anatomy of the Alzira Velano University Hospital wherethe percentage of the reepithelialization of the tissues was evaluated The data were submitted to the Student´s t-test and analysis of variance (ANOVA) - p< 0,05 with significant differences between the following variables and groups Longitudinal Axis TYRxCYR CYRxCOR TORxCOR Transversal Axis TYRxTOR TYRxCYR ImageLab TYRxTOR CYRxCOR CORxTOR CYRxTYR in reepithelialization TORxTYR TORxCOR TYRxCYR The treatment with low potency laser (660nm)with 3 joules during seven consecutive days was efficient in enhancing the reepithelialization of tissues in both young and old animals Therefore the aged tissues respond like the young ones to laser therapy The approximation of the wound borders is not always the only variable correlated to cicatrizacion No damaging effects occur in the aged tissues with low potency laser therapy